Influence of Bank Health Ratio on Financial Performance of Islamic Commercial Bank - Edi Komara (Jurnal Ilmu Manajemen & Ekonomika, 2017)
This study aims to analyse the influence of bank health ratios on the financial performance of Islamic Commercial Banks using the ratio of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) ratio, Operating Expenses Operating Income ratio (OEOI), against Islamic Commercial Bank’s profitability represented by Return on Asset ratio (ROA). The population used in this study is the financial statements of Islamic Commercial Banks period 2015 until 2017. Types of quantitative data with library data collection techniques, and documentation. Technical analysis of data using multiple linear regression analysis with the help of SPSS 20 program. The results showed that health variables (CAR, LDR, and OEOI) simultaneously affect the Financial Performance of Islamic Commercial Banks. Partially CAR has no significant effect on ROA, LDR has no significant effect on ROA. The effect of OEOI on ROA is partial.